Effects of exercise training on skeletal muscle mitochondrial outcomes in type 2 diabetes: a systematic review and meta-analysis - Zhu, Wenning; Zhou, Zhangxu; Sun, Jingyao; Si, Juncheng (Frontiers in Physiology, 2025)
BackgroundSkeletal muscle mitochondrial dysfunction is a key driver of insulin resistance and disease progression in type 2 diabetes mellitus (T2DM), while exercise training has shown potential to improve mitochondrial function. However, existing studies focus on single exercise modalities, lack systematic synthesis of mitochondrial mechanisms, and exhibit conflicting results, highlighting the need for a comprehensive meta-analysis.MethodsSystematic searches were conducted in PubMed, Web of Science, and Scopus for studies involving T2DM patients (≥40 years) with exercise as the primary intervention and mitochondrial outcomes. Methodological quality was assessed via the TESTEX scale, with meta-analysis performed using Stata 17.0.ResultsA total of 18 studies (394 participants, 272 in training groups) were included. Exercise significantly enhanced mitochondrial oxidative capacity (SMD = 0.61, 95% CI [0.30, 0.92], driven by citrate synthase [CS] and COX-II), antioxidant capacity (SMD = 1.18, 95% CI [0.50, 1.86], mainly via SOD2), and fusion marker MFN2 (SMD = 0.96, 95% CI [0.63, 1.29]). It tended to increase mitochondrial content (SMD = 0.50, p = 0.091) but with no significant mtDNA/PGC-1α changes. Effective modalities included long-term moderate aerobic training, short-term HIIT, and long-term resistance/combined training. Antidiabetic medications’ potential interference was underassessed.ConclusionModerate-to-high intensity exercise selectively improves skeletal muscle mitochondrial function in T2DM, particularly oxidative capacity (via CS/COX-II), antioxidant capacity (via SOD2), and mitochondrial fusion (via MFN2). The effect on mitochondrial content is non-significant, and the influence of antidiabetic medications requires further investigation.Systematic Review RegistrationIdentifier CRD42024579581.